On the birthday problem: some generalizations and applications - P. N. Rathie; P. Zörnig (International Journal of Mathematics and Mathematical Sciences)
We study the birthday problem and some possible extensions. We discuss the unimodality of the corresponding exact probability distribution and express the moments and generating functions by means of confluent hypergeometric functions U(−;−;−) which are computable using the software Mathematica. The distribution is generalized in two possible directions, one of them consists in considering a random graph with a single attracting center. Possible applications are also indicated.